Creating a guide for reflective practice: applying Dewey's reflective thinking to document faculty scholarly engagement. Issue 4 (3rd July 2020) - Greenberger, Scott W.
ABSTRACT: This article introduces the creation of a guide for reflective practice to document faculty scholarly engagement. As the editor for a journal designed to showcase scholarship of application and integration, I recognized the need for a guide to help faculty structure reflective practice and document their practical and scientific contributions. John Dewey's seminal framework on reflective thinking was used as a conceptual scaffolding to create the guide. There is a discussion of the challenges in interpreting Dewey's work in creating the guide, and I explain choices made that deviate from Dewey's original work on reflective thinking. I recommend expanding the guide to a method that education researchers or scholar-practitioners could use to systematically inquire about problems of practice.